What has been the progress in addressing financial risk in Uganda? Analysis of catastrophe and impoverishment due to health payments - Brendan Kwesiga; Tom Aliti; Pamela Nabukhonzo; Susan Najuko; Peter Byawaka; Justine Hsu; John E. Ataguba; Grace Kabaniha (BMC, 2020)
Abstract Background Monitoring progress towards Universal Health Coverage (UHC) requires an assessment of progress in coverage of health services and protection of households from the impact of direct out-of-pocket payments (i.e. financial risk protection). Although Uganda has expressed aspirations for attaining UHC, out-of-pocket payments remain a major contributor to total health expenditure. The aim of this study is to monitor progress in financial risk protection in Uganda. Methods This study uses data from the Uganda National Household Surveys for 2005/06, 2009/10, 2012/13 and 2016/17. We measure financial risk protection using catastrophic health care payments and impoverishment indicators. Health care payments are catastrophic if they exceed a set threshold (i.e. 10 and 25%) of the total household consumption expenditure. Health payments are impoverishing if they push the household below the poverty line (the US$1.90/day and Uganda's national poverty lines). A logistic regression model is used to assess the factors associated with household financial risk. Results The results show that while progress has been made in reducing financial risk, this progress remains minimal, and there is still a risk of a reversal of this trend. We find that although catastrophic health payments at the 10% threshold decreased from 22.4% in 2005/06 to 13.8% in 2012/13, it increased to 14.2% in 2016/17. The percentage of Ugandans pushed below the national poverty line (US$1.90/day) has decreased from 5.2% in 2005/06 to 2.7% in 2016/17. The distribution of both catastrophic health payments and impoverishment varies across socio-economic status, location and residence. In addition, certain household characteristics (poverty, having a child below 5 years and an adult above 60 years) are more associated with the lack of financial risk protection. Conclusion There is need for targeted interventions to reduce OOP, especially among those affected so as to increase financial risk protection. In the short-term, it is important to ensure that public health services are funded adequately to enable effective coverage with quality health care. In the medium-term, increased reliance on mandatory prepayment will reduce the burden of OOP health spending further.